1993
DOI: 10.1002/bdd.2510140404
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elimination and hepatic concentration of conjugation‐ metabolite of valproate in guinea‐pigs

Abstract: The plasma clearance and metabolic rate characteristics of valproic acid (VPA) were studied using guinea-pigs placed on various (0.08-9 mumol ml-1 = 11-1303 micrograms ml-1) steady-state plasma concentrations (Css) by constant intravenous (i.v.) infusion. The total clearance (CL) was significantly decreased at plasma concentration of 0.61 mumol ml-1 (88 micrograms ml-1). The metabolic clearance of VPA was apparently biphasic. The maximum metabolic rate (Vmax) and the Michaelis-Menten constant (Km) for the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…After the intravenous administration of VPA, its AUC0-4 h (303 mg h ml ) was similar to the reported values, 225 mg h ml -1 (Yu et al, 1993) and 330 mg h ml -1 (Dickinson et al, 1979), at the same intravenous dose. The formation of toxic metabolites, 4-VPA and 2,4-VPA were rapid; they were detected in the plasma from the second blood sampling time point (10 min).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…After the intravenous administration of VPA, its AUC0-4 h (303 mg h ml ) was similar to the reported values, 225 mg h ml -1 (Yu et al, 1993) and 330 mg h ml -1 (Dickinson et al, 1979), at the same intravenous dose. The formation of toxic metabolites, 4-VPA and 2,4-VPA were rapid; they were detected in the plasma from the second blood sampling time point (10 min).…”
Section: Resultssupporting
confidence: 88%
“…VPA is metabolized to 4-VPA via microsomal cytochrome P450-mediated dehydrogenation and 4-ene-VPA is further bioactivated through mitochondrial b-oxidation to 2,4-diene-VPA (Tang and Abbott, 1997). The decreased plasma exposure of 4-VPA seems to be due to the saturation of microsomal cytochrome P450 and liver distribution (Brouwer et al, 1993;Yu et al, 1993).…”
Section: Resultsmentioning
confidence: 95%
“…It obeys Michaelis-Menten type kinetics Yu & Shen 1996), with the Michaelis-Menten constant (K m ) in the middle of the therapeutic concentration range (Yu & Shen 1996), and the maximum biotrans-formation rate (V max ) approximating a high therapeutic dosing rate . Non-linear biliary excretion (Dickinson et al 1979;Yu et al 1993) and urinary recovery (Granneman et al 1984b) of VPAG have been reported. Biliary VPA is equivalent to, but biliary VPAG decreases relative to, the liver concentration of VPA .…”
Section: Introductionmentioning
confidence: 99%